Factors Affecting Students' Online Shopping Attitude and Purchase Intention - Delafrooz, Narges (2009)
The ever-increasing use of the Internet in Malaysia provides a developing prospect for E-marketers. Such marketers’ awareness of the factors affecting Malaysian’s shopping attitudes and intentions is crucial to further develop their marketing strategies in converting potential customers into active ones, while maintaining the existing online customers. Purchase intention is an important determinant of online shopping behavior and represents the best estimates of future behavior available to market researchers. From an e-commerce perspective, understanding of the Theory of Reasoned Action, Theory Planned Behavior, and Technology Acceptance Model could provide a valid basis for explaining and predicting consumers’ intentions towards adopting online shopping behavior.This study sets out to examine the factors influencing students’ online shopping attitudes and intentions at Universiti Putra Malaysia (UPM) through a five-pint Likert scale self-administered questionnaire. The instrument has demonstrated acceptable levels of internal consistency, reliability, and content validity according to previous documented studies. A sample of 370 students was selected among postgraduate students at Universiti Putra Malaysia. Descriptive analysis, Pearson correlation, partial correlation, multiple regression, and path analysis were employed to achieve the objectives of the study. The results of the study showed that the level of online shopping intention was relatively high and direction of attitude towards online shopping was positive among the postgraduate students. Moreover, it was found that utilitarian orientation and hedonic orientation, perceived benefits and demographic characteristics (gender, age, and income) were significantly and positively correlated with the attitude towards online shopping. In addition, the result revealed that the perceived behavioural control and attitude were significantly and positively correlated with online shopping intention. Finally, the finding identified that the trust in the construct of perceived behavioural control and attitude had higher direct effect whereas utilitarian orientation, convenience, prices and wider selection, and income had higher indirect effect on the students’ online shopping intention.